Validation of “Clinical Red Flags” for RA-ILD in an Italian cohort - Cela, Eneida; Bonini, Chiara; Cavalli, Francesco; Luciano, Alessandra; Kroegler, Barbara; Ora, Josuel; Bergamini, Alberto; Chiocchi, Marcello; Rogliani, Paola; Chimenti, Maria Sole; Conigliaro, Paola (Frontiers in Medicine, 2025)
IntroductionRheumatoid arthritis (RA) is a systemic inflammatory disease, characterized by articular and extra-articular manifestations, including Interstitial Lung Disease (ILD). An early diagnosis of ILD can be essential in improving disease outcome. A clinical practice checklist has previously been proposed, highlighting red flags in signs and symptoms suggestive of RA-ILD. Our aim was to validate the “checklists of red flags signs or symptoms suggestive of RA-ILD” in our cohort of RA patients, by assessing the diagnostic utility of dyspnea, cough, and crackles, both individually and in combination.MethodsWe performed a retrospective study including medical charts of consecutive RA patients fulfilling 2010 ACR/EULAR classification criteria. The diagnosis of RA-ILD was based on the chest HRCT exam. The primary symptoms and signs of ILD, namely cough, crackles, and dyspnea, were considered separately and in combination to determine diagnostic performance metrics.ResultsOur cohort included 107 patients with RA, from which 55 (51.4%) with a diagnosis of RA-ILD. Female patients were predominant in both RA-ILD and No-ILD groups (56.4 and 82.6% respectively), with a significantly higher proportion in the latter (p = 0.0036). Dyspnea alone demonstrated a good diagnostic utility for RA-ILD with a sensitivity of 63.5% and specificity of 60%, PPV of 60% and an NPV of 63.5%, (p = 0.0203). Additionally, crackles exhibited the highest sensitivity among the individual symptoms (66.7%), a specificity of 57.4% and a significant association with RA-ILD (p = 0.0265). The presence of either dyspnea or crackles confirmed their strong association with RA-ILD (p = 0.0066), with the highest level of accuracy (63.5%) and specificity (63.8%). Also, the combination of cough or dyspnea was significantly associated with RA-ILD (p = 0.0111). A strong correlation was observed between RA-ILD and the presence of both crackles and dyspnea (p = 0.0351). When the three symptoms were combined, the sensitivity was 64.3%, the specificity was 53.2%, the PPV was 32.7%, and the NPV was 81%, but did not reach statistical significance (p = 0.1284).ConclusionOverall, crackles and dyspnea were the most significant markers of RA-ILD, both individually, and in combination. This study confirms that the red flags previously identified, especially in combination, show an important accuracy and reliability as clinical biomarkers in the early detection of RA-ILD.